Professor Mario Cazzola: prospect of the COPD medicine - He, Melanie C. (Journal of Thoracic Disease, 2014)
Mario Cazzola is a Professor of Respiratory Medicine and Director of the Postgraduate School of Respiratory Medicine at the University of Rome ‘Tor Vergata’, Rome, Italy, where he is also Chief of the Respiratory Clinical Pharmacology Unit. He is Honorary Professor at the Sackler Institute of Pulmonary Pharmacology, GKT School of Biomedical Sciences, London, UK. He is the author or co-author of almost 500 scientific papers.